Effects of a Dried Neem Leaf Extract on the Growth Performance, Meat Yield and Meat Quality in Skeletal Muscle of Broiler Chickens Under High-Temperature Conditions - Nakamura, Kiriko; Katafuchi, Ayumi; Shimamoto, Saki; Ogawa, Goichiro; Khandelwal, Nikhil; Tatsugawa, Kenji; Fujita, Yoshikazu; Ohtsuka, Akira; Ijiri, Daichi (Frontiers in Animal Science, 2022)
We aimed to examine the effects of cyclical high ambient temperature (HT) and dried Neem (Azadirachta indica) leaf extract (DNE) supplementation on the growth performance, muscle lipid peroxidation level, and muscle drip loss of broiler chickens. Twenty-four 15-day old broiler chickens (Chunky strain ROSS 308) were divided into four treatment groups that were fed diets with or without 2.0% DNE under thermoneutral (25 ± 1 °C) or cyclical HT (35 ± 1 °C for 8 h/day) conditions. Supplementation of DNE did not affect the growth performance of the chicks, but HT reduced their feed intake, the weights of breast muscle and heart. In addition, supplementation with DNE ameliorated the negative effects of cyclical HT on feed intake and breast muscle mass. Furthermore, cyclical HT increased the malondialdehyde (MDA) concentration and drip loss over 48 h of storage of the breast muscle, and these effects were ameliorated by DNE. Collectively, we conclude that dietary supplementation with DNE reduces the muscle MDA concentration and drip loss of broiler chickens kept under HT conditions.